Salário-educação e o princípio da equidade na federação brasileira : desequilíbrio distributivo na esfera estadual e suas implicações - Oliveira, Adriano José Germano de (2015)
This work aims to analyze the dynamics of distribution of state share / municipal for education for financing basic education in the face of the principle of equity, from the constitutional and infra-constitutional criteria. The rationale for analyzing the share for education that is distributed to the states and their municipalities occurs because of this value is proportional to the amount raised from this tax for each federated state, which aroused the interest in investigating whether this systematic conforms to the principle of equity Constitution expressly provided for the distribution of public resources invested in compulsory education. Therefore, we use in the development of this analysis the Federal Constitution of 1988 and the whole infra legislation regulating the tax and its distribution, as well as the theoretical frameworks of Emerson Gabarra and Gilberto Bercovici to the grounds of the principle of equity. Our research is descriptive, how to study; literature concerning the collection of data; and exploratory, as the goal. With the adoption of theoretical and methodological approach described above, and using said theoretical basis of analysis, obtained as a result of this work the realization of considerable differences between the absolute and relative values for education received by the states and their municipalities, as well as lack of constitutional rule that determines the distribution of the share of that tax in proportion to the revenues of each state, which allowed us to infer the failure of the constitutional principle of equity in the said distribution.